Evaluation of CD57+ cells in oral squamous cells carcinoma and their relationship with clinicopathological parameters - Lopes, Maria Luiza Diniz de Sousa; Barros, Caio César da Silva; Medeiros, Maurília Raquel de Souto; Miguel, Márcia Cristina da Costa; Souza, Lélia Batista de; Alves, Pollianna Muniz; Silveira, Éricka Janine Dantas da (Journal of Oral Diagnosis, 2017)
Introduction: The immune response occurring in the tumor microenvironment is very complex. Surface molecule CD57 can be expressed by natural killer cells and/or activated T lymphocytes, which are key cellular types in the cancer immunity. Objectives: This study investigated CD57 immunoexpression in immune cells of oral squamous cell carcinoma (OSCC) and verified its association with clinicopathological features. Methods: Paraffin-embedded sections of 45 OSCCs were submitted to morphological and immunohistochemical analysis using anti-CD57 antibody. Relationship between the expression of CD57 and clinicopathological parameters (age, metastasis to regional lymph nodes, clinical stage and histopathological grade of malignancy) was verified by Pearson’s Chi square, and Fisher exact statistical tests. Results: The majority (64.4%) of the OSCCs analyzed affected subjects of male gender and over 40 years old (68.9%). There was a significant association between histological grade of malignancy and presence of lymph node metastasis, as well as clinical stage (p<0.05). Conclusions: The results suggest that CD57+ cells immune cells infiltration is a consistent finding in OSCC, regardless of clinicopathological features of these tumors.